2021
DOI: 10.20960/nh.03447
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of rs3211938 polymorphism at CD36 to glucose levels, oxidized low-density lipoproteins, insulin resistance, and body mass index in Mexican mestizos with type-2 diabetes from western Mexico

Abstract: Contribución del polimorfismo rs3211938 de CD36 a los niveles de glucosa, las lipoproteínas de baja densidad oxidadas, la resistencia a la insulina y el índice de masa corporal en mestizos mexicanos con diabetes de tipo 2 del occidente de México Contribution of rs3211938 polymorphism at CD36 to glucose levels, oxidized low-density lipoproteins, insulin resistance, and body mass index in Mexican mestizos with type-2 diabetes from western Mexico 10.20960/nh.03447 OR 3447 Contribution of rs3211938 polymorphism at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The role of CD36 in IR and T2D has been controversial; some studies reported that increased circulating CD36 levels were observed in IR states including T2D 3,5 ; meanwhile, studies in Japanese patients with diabetes with CD36 deficiency showed highest levels of glucose, hemoglobin (Hb) A1c, high-density lipoprotein cholesterol (HDL-c), and body mass index (BMI) compared to non-diabetic CD36 deficient subjects 6 . With the purpose of complementing our previous findings, where we found that the CD36 rs3211938 TG genotype is associated with high glucose, ox-LDL, HDL-c levels, and IR in T2D Mexican patients 7 , we conducted an analysis to evaluate whether the adiposity-related parameters and lipids are associated with peripheral blood mononuclear cells (PBMCs) CD36 expression in T2D and non-T2D normoglycemic (NT2D) individuals with normal weight (NW) and obesity (OW) from West México.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The role of CD36 in IR and T2D has been controversial; some studies reported that increased circulating CD36 levels were observed in IR states including T2D 3,5 ; meanwhile, studies in Japanese patients with diabetes with CD36 deficiency showed highest levels of glucose, hemoglobin (Hb) A1c, high-density lipoprotein cholesterol (HDL-c), and body mass index (BMI) compared to non-diabetic CD36 deficient subjects 6 . With the purpose of complementing our previous findings, where we found that the CD36 rs3211938 TG genotype is associated with high glucose, ox-LDL, HDL-c levels, and IR in T2D Mexican patients 7 , we conducted an analysis to evaluate whether the adiposity-related parameters and lipids are associated with peripheral blood mononuclear cells (PBMCs) CD36 expression in T2D and non-T2D normoglycemic (NT2D) individuals with normal weight (NW) and obesity (OW) from West México.…”
Section: Introductionsupporting
confidence: 74%
“…We analyze 115 subjects in a cross-over study classified in NT2D adults and patients with T2D (n = 58 and n = 57, respectively) from a previous study. The protocol was carried out in a period of 8 months (June 2018-February 2019) 7 . The NT2D subjects were recruited from open urban population and the T2D from the external consultation of the Endocrinology Specialty Service of the Hospital Civil Dr. Juan I. Menchaca, at Guadalajara, Jalisco, Mexico.…”
Section: Subject Assessmentmentioning
confidence: 99%
“…Previous studies have supported the involvement of mutations in SR genes with multiple diseases including infectious diseases (7,8), cardiovascular diseases (9,10), metabolic disorders (11,12), and neurodegenerative disorder (13). There are only two studies on the association between SR gene polymorphisms and TB in the Gambian and Chinese populations (14,15).…”
Section: Introductionmentioning
confidence: 99%